Evaluation of the Tuberculosis Control Program in a state of the Brazilian Amazon Region - Regina Lima Ferreira, Melisane; Laine de Paula Andrade, Rubia; de Oliveira Barros, Nilda; Fragoso da Silva, Letícia Auxiliadora; Terenciani Campoy, Laura; Monroe, Aline Aparecida; Halax Orfão, Nathalia (O Mundo da Saúde, 2022)
The evaluation of the Tuberculosis Control Program contributes to identifying the difficulties that permeate the implementation of public policies defined for the control of the disease. Thus, this study aimed to evaluate the performance of Municipal Tuberculosis Control Programs in Rondônia and identify aspects associated with such performance. An ecological study was carried out in 39 municipalities in the state in 2018. Performance indicators of municipal programs were calculated for further cluster analyses, which grouped them according to performance. The multiple correspondence analysis was used to identify variables (demographic, social, epidemiological, and those related to the health system) associated with the formed groups. The results showed that cluster 1, with 25 municipalities, displayed a regular performance and was associated with a small and large population, high incidence of tuberculosis and AIDS, and a low coverage of the Community Health Agents Program and the Family Health Strategy. Cluster 2, with 10 municipalities, presented an unsatisfactory performance and was associated with medium population size, low incidence of tuberculosis and AIDS, high coverage of the Community Health Agents Program and the Family Health Strategy, absence of indigenous areas, and worse social indicators. Cluster 3, with four municipalities, demonstrated a satisfactory performance and was associated with the presence of indigenous areas and better social indicators. It is possible to conclude the need for more attention given to social inequalities in the municipalities with the worst performance as well as to a greater role of Primary Health Care in facing the disease.